Differential Effects of Calorie Restriction and Exercise on the Adipose Transcriptome in Diet-Induced Obese Mice - Karrie E. Wheatley; Leticia M. Nogueira; Susan N. Perkins; Stephen D. Hursting (Journal of Obesity)
We tested the hypothesis that obesity reversal by calorie restriction (CR) versus treadmill exercise (EX) differentially modulates adipose gene expression using 48 female C57BL/6 mice administered a diet-induced obesity (DIO) regimen for 8 weeks, then randomized to receive for 8 weeks either: (1) a control (AIN-76A) diet, fed ad libitum (DIO control); (2) a 30% CR regimen; (3) a treadmill EX regimen (with AIN-76A diet fed ad libitum); or (4) continuation of the DIO diet. Relative to the DIO controls, both CR and EX reduced adiposity by 35–40% and serum leptin levels by 80%, but only CR increased adiponectin and insulin sensitivity. Gene expression microarray analysis of visceral white adipose tissue revealed 209 genes responsive to both CR and EX, relative to the DIO group. However, CR uniquely altered expression of an additional 496 genes, whereas only 20 were uniquely affected by EX. Of the genes distinctly responsive to CR, 17 related to carbohydrate metabolism and glucose transport, including glucose transporter (GLUT) 4. Chromatin immunoprecipitation assays of the Glut4 promoter revealed that, relative to the DIO controls, CR significantly increased histone 4 acetylation, suggesting epigenetic regulation may underlie some of the differential effects of CR versus EX on the adipose transcriptome.